2x4 - 26x2 + 72 = 0
Divide each side by 2:
x4 - 13x2 + 36 = 0
(x2 - 9) (x2 - 4) = 0
A). x2 - 9 = 0
B). x2 - 4 = 0
______________________
A). (x + 3) (x - 3) = 0
x = +3
x = -3
B). (x + 4) (x - 4) = 0
x = +4
x = -4
2x^2y^3(4x^2 - 3xy + 1)
2 to the 4th times 5 squared
Yes.
184 equals 104,976
1
2222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222
This doesn't make any math sense:2⁴ - 1 + 21 = 14 = 7 +3 x 5
2x^2y^3(4x^2 - 3xy + 1)
(X2) (X2) = X4 x squared multiplied by x squared is x raised to the 4th power.
If that's +14x + 3, the answer is (2x + 3)(4x + 1)
(3y2)4*3y2*3y2*3y2*3y2 = 38*y16 = 6561y16
16 to the 4th power, or 16 x 16 x 16 x 16 = 65,536
3 to the 4th power 9 squared
104 equals 10,000
the 4th root of 80 equals 2.9907
2 to the 4th times 5 squared
x^2 * x^2 = x^4. When multiplying two variables with exponents, you simply have to add the exponents together, keeping the same variable. So in this case you'd add 2+2 to get a variable to the 4th power.